PEMANFAATAN AKUN BELAJAR.ID DALAM MANAJEMEN EVALUASI PEMBELAJARAN BERBASIS DIGITAL - Supratman Zakir; Hendri (CV. ALIM'SPUBLISHING, 2024)
Abstract. The Belajar.id site is a medium provided by the Ministry of Education, Culture, Research and Technology, which helps students and teachers in accessing teaching and learning needs, face-to-face or remotely. The method used in this research is a qualitative research method through surveys with data collection techniques via Google forms. This was done because the research time was only two months. Apart from that, data collection was relatively fast, because the respondents were 80 final grade students at elementary and junior high school levels, 30 sixth grade teachers, 80 school principals, and 80 school operators. With a total of 270 respondents. The use of the Belajar.id account is not only focused on one tool, but also on several variations of tools such as Google Classroom, Google Form and Google Meet.